The Perceptions and Attitudes of Medical Students towards Orthopaedic and Trauma Surgery Teaching in Makurdi, Nigeria - Elachi, Itodo Cornelius; Kotor, Joseph Namgwa; Yongu, Williams Terhemen; Efu, Michael Enokela (Nigerian Journal of Orthopaedics and Trauma, 2020)
Aim: The aim of this study was to assess the perceived educational value of orthopaedic and surgery learning opportunities among medical students and to evaluate the students’ motivating factors in pursuing a future career in the specialty. Methodology: A questionnaire was designed to assess undergraduate medical students’ perception of learning environments in orthopaedic and trauma surgery, career intent and motivation towards a future career in the specialty. A 5‑point Likert scale was employed. Results: Seventy‑four students completed the questionnaire. Learning opportunities considered useful for orthopaedic and trauma surgery were bedside teaching with a consultant (n = 39, 52.7%), seeing patients in clinic (n = 36, 48.6%) and formal lectures (n = 35, 47%). Fifteen respondents (20.3%) expressed an interest in pursuing a career in the specialty, with watching or assisting open surgery being the most significant motivating factor (P = 0.001) for choice of the specialty. Conclusion: Bedside teaching with a consultant and seeing patients in outpatient clinics were found to be the most useful learning environments. A fifth of the respondents indicated an interest in a future orthopaedic and trauma surgery career, with watching or assisting open surgery being the most statistically significant motivating factor. Students may be better served incorporating the findings in future curriculum design.